Trust over repeated interactions: Majority group members generalize more from interactions with non-coethnic partners - Siyeona Chang; Maria Abascal; Delia Baldassarri (PLoS ONE, 2026)
People increasingly live in complex, heterogeneous communities characterized by differentiation, where groups may lack the shared history and/or close ties that can nurture trust in more traditional communities. How does trust generalize from an interaction with one stranger––either trustworthy or untrustworthy––to subsequent interactions with other strangers? Does trust generalize more from or toward interactions with outgroup members than ingroup members? And, does an interaction with one stranger affect someone’s willingness to interact with strangers from the same group moving forward? This study examines these questions using a repeated trust game in which 1,255 US White adults were paired with a White or Latino partner who behaved in a trustworthy or untrustworthy way. Results reveal that participants paired with an untrustworthy outgroup member in the first round were less likely to choose an outgroup partner for the second round. This effect is pronounced among participants who likely were uncertain initially about their partner’s behavior. These participants also gave less in the second round when their first-round partner behaved in an untrustworthy way. Our findings highlight the need to treat a willingness to interact with outgroup members as an outcome of intergroup contact.